Cautioned statements: a legal study under Section 113 Criminal Procedure Code / Johar Othman - Othman, Johar (Faculty of Law, 1987)
Statement given by an accused person during police investigation has raised a lot of questions among the public and the legal profession. A person giving a statement has to be cautioned either before or after the giving of the statement. If the caution is not administered then the statement would be inadmissible under S 113 of Criminal Procedure Code. Even if the statement given is cautioned it would still be inadmissible if it was made involuntarily or the requirements in making the statement were not fulfilled. If the prosecution alleged that it was voluntarily how must he prove it? Can a trial-within-a-trial be held to determine the voluntariness of that cautioned statements? If the cautioned statements is admissible who may use it? Whether the prosecution alone may use it or is it the accused also has the right to it. This project paper is concerned on the cautioned statement under S 113 of Criminal Procedure Code because most cases involving cautioned statements are criminal cases under Criminal Procedure Code. The writer will make a study of the cautioned statements under Criminal Procedure Code and try to comment in every possible aspects.